Anti-Corruption Values Civilization Management Model in the Program of Strengthening Character Education in Public Primary Schools in Gorontalo Regency - Irmawati Duko Ishak (International Journal of Science and Society, 2019)
This study is about a model of civilizing anti-corruption values in the implementation of programs to strengthen character education in public elementary schools in the district. Gorontalo. The main target of this research is to design a model of the civilization of anti-corruption values in the implementation of character education strengthening programs that can produce products in the form of books to guide educators, parents and the public, especially in Gorontalo district in implementing anti-corruption values which lead to the creation of anti-corruption characters. This research applies the research and development approach. This research also answers specific questions of practical problems through "applied research" to improve educational practices. The study, conducted in January to July 2019, began with collecting initial information through observations in public elementary schools in Gorontalo district, and from various other sources such as the education office, principals, educators, students, parents, and the community. The implementation of the research through stages, preparation begins with the initial observation of the implementation of strengthening character education in schools, collecting data, interviewing analyzing data, reviewing and verifying data, preparing reports, and publicizing. This research uses a data triangulation technique that is combining 3 data collection techniques (observation, interview, and documentation) data analysis carried out during the process in the field together with data collection.